How do people with cancer and palliative care needs understand and contribute to the management of communication surrounding their care?. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Jarrett, Nikki; Porter, Katerina; Addington-Hall, Julia; Corner, Jessica; Davis, Carol; Duke, Sue; Lathlean, Judith
Abstract : Background: The authors have very limited knowledge regarding how people with cancer and palliative care needs understand and contribute to the often complex networks and pathways of communication between the different people, teams and locations involved in their care. Aim: Explore how people with cancer and palliative care needs understand and contribute to the communication surrounding their care. Method: During indepth interviews (n=24; mean length 65 min), patients were asked to discuss the communication that surrounds their care. Framework analysis of the transcribed interviews considered patients' understanding of the communication surrounding them, and any contributions they make to facilitating or managing that communication. Results: Patients (15 female, 9 male; age range: 48–85) had a wide range of primary tumours (mean time since diagnosis: 9.5 months; range: 0.5–61 months). All were described as receiving or needing specialist or generalist palliative care at the time of recruitment (through General Practice (n=5); Hospital Specialist Palliative Care Team (n=8); Specialist Palliative Care Unit (n=11)). Analysis reveals variation in the extent of patients' understanding of, and contribution to, the management of the communication surrounding their care, including 'active involvement', 'understanding', 'storing information', 'opportunism' and 'delegation'. Some patients are less involved, with approaches including 'cooperation' and 'reluctance to communicate'. Some patients who attempt 'active involvement' encounter 'barriers' to achieving this. Conclusion: It is concluded that patients demonstrate a variety of ways of dealing with, understanding, and contributing to the communication surrounding their care. Example cases illustrate the range of approaches some individuals appear to use, compared with those that appear available to other patients. These are explored in terms of factors such as patient disposition, 'insider knowledge', uncertainty in less-common cancer, 'behind the scenes' communication, and the complexity of some care packages. These findings present implications for facilitating supported self-management while recognising/minimising patient burden.